Synthesis and characterization of heteronanostructured Ag nanoparticles/MoO3 nanobelts composites - Sinaim H. (2014)
MoO3 nanobelts have been successfully synthesized by a conventional hydrothermal method at 180 °C for 24 h, and followed by sonication of Ag+ and MoO3 nanobelts in 1,2-propanediol to produce Ag/MoO3 nanocomposites. The as-synthesized heteronanostructured Ag/MoO3 composites were investigated by XRD, Raman, SEM, TEM and UV-visible absorption analyses. XRD, SEM and TEM results show that the as-synthesized Ag/MoO3 composites were composed of orthorhombic α-MoO3 nanobelts with good dispersion of cubic Ag nanoparticles on the surfaces. The optical property presented UV-visible absorption peaks at 231 and 312 nm for the Ag/MoO3 nanocomposites. Furthermore the decolorization of rhodamine-B (RhB) for the synthesized Ag nanoparticles deposited on MoO3 nanobelts as a photocatalyst was investigated. © 2011 Elsevier B.V. All rights reserved.